Popular justice and territorial resistance in the Peruvian Andes: the case of Huanta - Huayhua Lévano, Fernando Gari; Cardenas Morales, Bruno Kadafi; Ñaupari Molina, Rubén; Oré Gálvez, Saríah Fanny; Quispe Quispe, Alex; Coronado Illanes, Ivet Danitza; Huayhua Aguirre, Fernando Félix; Tacuri Gamboa, Amilcar; Ramos Malpica, Jhon Ivan (Frontiers in Sociology, 2025)
Huanta, known as “The Emerald of the Andes,” is a historical epicenter of radical mobilization in southern Peru, where resistance has emerged against a state perceived as absent and repressive. This study aims to analyze the radicalization of protest through three key events: the 1969 Rebellion opposing educational reforms under Velasco Alvarado’s regime; the burning of the Provincial Prosecutor’s Office in 2022 as an act of popular justice; and the 2024 indefinite strike in the Razuhuillca watershed against mining expansion. Using a qualitative approach based on in-depth interviews, documentary analysis, and thematic coding, this research identifies three dimensions: historical memory of resistance, crisis of state legitimacy, and communal territorial defense. Drawing upon theories of structural, symbolic, necropolitical, and territorial violence, the study explores how multiple forms of exclusion intersect to produce radicalized collective action. The findings reveal that radicalization in Huanta is rooted in intergenerational memory, community cohesion, and self-governance, rather than spontaneous impulses. This suggests that plebeian protest is not an anomaly but a structural response to exclusion and state violence, offering insights into broader dynamics of resistance and community governance in the Peruvian Andes.